Temperature Field Analysis and Cooling Structure Design of Ironless Permanent Magnet Synchronous Linear Motor - Lu, Xiaoting; Li, Yang; Chen, Zailiang (Recent Advances in Electrical & Electronic Engineering, 2022)
Objective: Ironless, permanent magnet, synchronous linear (IPMSL) motors are applied widely in precision servo control for the nonexistence of cogging forces and comparatively small fluctuations in thrust and speed. Methods: The air and water cooling structures are designed by assuming the heat loss in the motor operations is the source for the distribution of the temperature field in the analysis under natural cooling. Results and Conclusion: The temperature fields of the linear motor under the two cooling modes are compared and analyzed, which helps monitor the temperature of linear motors during development and operations.
Keywords: cooling modes